Inferring the Unofficial Incomes of Officials from Home Ownership - Deng, Yongheng; Wei, Shang-Jin (Management Science, 2025)
We estimate the size of the likely unofficial income of the government official household by assessing the difference between the income necessary to explain their observed home purchase behavior and the official income. Using unique and comprehensive House Provident Fund and home purchases data between 2006 and 2013 in a large Chinese city, we reach three conclusions. First, an average official’s unofficial income is 83% of her official income; this percentage increases sharply with the official’s rank. Second, about 13% of the officials have an unofficial income, and the proportion also increases with rank. Third, government officials are not underpaid, and their unofficial incomes are not compensation for low government salaries. Additionally, evidence suggests that unofficial incomes have declined since the recent anticorruption campaign. An analysis of a separate crosscity data set corroborates the key conclusion. This paper was accepted by David Sraer, finance. Supplemental Material: The online appendix and data files are available at https://doi.org/10.1287/mnsc.2021.01725 .